On the Temperature Indices of Molecular Structures of Some Networks - Akbar Jahanbani; Rana Khoeilar; Murat Cancan (Journal of Mathematics)
The topological index is a molecular predictor that is commonly supported in the research of QSAR of pharmaceuticals to numerically quantify their molecular features. Theoretical and statistical study of drug-like compounds improves the drug design and finding work-flow by rationalizing lead detection, instant decision, and mechanism of action comprehension. Using molecular structure characterization and edge segmentation technique, we computed the general temperature topological indices for OTIS networks.